Balancing Inflammation: The Link between Th17 and Regulatory T Cells - Maggie L. Diller; Ragini R. Kudchadkar; Keith A. Delman; David H. Lawson; Mandy L. Ford (Mediators of Inflammation)
CD4+ T cell compartments in mouse and man are composed of multiple distinct subsets each possessing unique phenotypic and functional characteristics. IL-17-producing CD4+ T cells (Th17 cells) represent a distinct subset of the CD4+ T cell lineage. Recent evidence suggests that Th17 cells carry out effector functions similar to cytotoxic CD8+ T cells and play an important role in the clearance of extracellular pathogens and fungi. Th17 cell differentiation and function are closely related to the development and function of regulatory T cells (TREG). The balance between these two cell populations is essential for immune homeostasis and dysregulation of this balance has been implicated in a variety of inflammatory conditions including autoimmunity, allograft rejection, and tumorigenesis. Emerging evidence reports a significant amount of plasticity between the Th17 and regulatory T cell compartments, and the mechanisms by which these cells communicate and influence each other are just beginning to be understood. In this review, we highlight recent findings detailing the mechanisms driving Th17 and TREG plasticity and discuss the biologic consequences of their unique relationship.